Enhancing exercise performance through ischaemic preconditioning - Cocking, S. (Liverpool John Moores University, 2019)
Ischaemic preconditioning (IPC) is an intervention whereby brief intermittent ischaemic episodes are induced in a limb (usually 4x5-minute arterial occlusion bouts, interspersed with 5-minutes of reperfusion) either at the site of interest (IPC), or at a distance from the site of interest (Remote; RIPC). Although originally linked to cardiology, recently studies have investigated the effects of IPC administered on a limb prior to exercise with some showing improvements in exercise performance. The overarching aim of the present thesis was to investigate how to optimise IPC to further enhance exercise performance. The optimal protocol of IPC on exercise performance was quantified by manipulating: 1. the number of cycles, 2. amount of muscle tissue, and 3. local vs Remote occlusion, which were applied in a randomized counterbalanced order in study 1 (Chapter 3). IPC dose, location and occlusion area differed prior to a 375 KJ time trial (TT) performance in 12 trained men. The traditional 4x5-min IPC stimulus resulted in the fastest TT time compared to SHAM [17 secs (90% CI: 0, 34 secs); P=0.097], but there was no benefit of applying a greater number of cycles [5 secs (-35, 26 secs); P=0.49] or employing unilateral IPC [18 secs (-11, 48 secs, P=0.29]. Local versus Remote cuff placement did not result in changes in TT time [0 secs (-16, 16 secs; P > 0.9]. Overall, regardless of location, the 4x5-minute dose seemed to provide the most benefit to exercise performance. The ability of IPC to enhance exercise capacity may be mediated through altering exercise-induced blood flow and/or vascular function. Study 2 (Chapter 4) investigated the blood flow response to exercise, using ultrasound, when exercise was preceded by a control (SHAM) condition, or either local or Remote (R)IPC in eighteen recreationally trained males. Vascular 4 function tests were also performed before SHAM and (R)IPC and at the end of exercise. IPC resulted in enlarged brachial artery diameter during exercise [0.016 cm (0.003 to 0.03 cm); P=0.016] compared to RIPC, but blood flow during exercise was similar between conditions. No changes in post-exercise vascular function were observed between conditions. Therefore, enhanced vasodilation following local (but not Remote) IPC, when performed prior to exercise, does not translate into increased blood flow during exercise nor impact post-exercise vascular function. IPC could alleviate deleterious muscle damage responses after exercise-induced muscle damage (EIMD; often lasting < 72 hours). Study 3 (Chapter 5) investigated whether IPC could negate eccentric exercise-induced reductions in torque production. Eleven recreationally trained males completed 200 repetitions of maximal eccentric contractions when preceded by IPC or SHAM performed in a randomized order, separated by a 9-week washout period. Muscle function tests were performed after IPC/SHAM prior to eccentric exercise and at 1-hour, 24-hours, 48-hours & 72-hours post-EIMD. Venous blood samples were taken at all time points. Greater maximal [15.2 N.m-1 (6.2 to 24.1); P=0.006] and mean [13.3 N.m-1 (5.3 to 21.3); P=0.007] torque production during a fixed angle voluntary maximal voluntary contraction (MVC) task and during a 60 deg·sec-1 [10.1 (4.9 to 15.3); P=0.002 & 9.8 N.m-1 (6.1 to 13.5; P < 0.005] isokinetic task were evident after IPC versus SHAM prior to eccentric exercise (EIMD). This was maintained throughout the (72-hour) muscle damage window. Lower cytokine (IL-6 and IL-1ra) were reported after IPC versus SHAM (P < 0.002, respectively). IPC resulted in greater overall HSP-27 & 32 levels (P < 0.01) whilst HSP-72 was lower (P=0.001) versus SHAM. Therefore, IPC can enhance maximal torque production during isokinetic dynamometry, before and after muscle damaging exercise and induce advantageous extracellular stress responses to EIMD in humans. 5 Study 4 employed IPC in a practical exercise-priming model, that aimed to maximise repeated sprint ability (RSA). Eleven trained cyclists performed 4 experimental visits in a repeated measures design. The "traditional" 4x5-minute local IPC (IPC) dose was compared to a SHAM condition (20 mmHg). IPC or SHAM were performed on two separate visits, each combined with either passive muscle heating (HEAT) on two visits, or thermoneutral (non-heated) insulation on two visits, prior to an "all out" repeated sprint task (10x6-second sprints with 24-seconds of recovery). There were no meaningful changes in 10x6-second average [12 (-7 to 31) watts; P=0.28] or peak [6 (-14 to 26) watts; P=0.62] power output following IPC versus SHAM. Additionally, no benefit was observed when muscle temperature was elevated in combination with IPC [5 (-14 to 19) watts; P=0.67], or separately to IPC [9 (-9 to 28); P=0.4] versus SHAM. Overall, it appears that IPC, nor (the combination of) muscle heating can positively impact RSA performance in trained cyclists versus a SHAM condition. The findings from this thesis suggest that using a "traditional" dose of 4x5-minute cycles, either on the legs or the arms, promote performance enhancements in aerobic tasks such as cycling TT performance. These potential performance improvements are likely not resultant from increased limb blood flow. IPC can also enhance muscle function following muscle damaging exercise and induce advantageous extracellular stress responses to EIMD. Nevertheless, IPC alone or when combined with local muscle heating likely has no meaningful enhancements in repeated sprint cycling performance. The findings from this thesis may help athletes to establish a better understanding of how IPC can be used prior to exercise